2020
DOI: 10.4149/km_2019_1_95
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and thermal stability of ZrB2 powder infiltrated by molten Cu and CuCr1Zr alloy

Abstract: Cu/ZrB2 and CuCr1Zr/ZrB2 composites were prepared by gas pressure infiltration technology. The ZrB2 powder was used as reinforcement. No interfacial reaction took place for Cu, or CuCr1Zr matrix as confirmed by transmission electron microscopy (TEM). The thermal stability of composites was very good, i.e. without any indication of possible disintegration. Composites exhibit high structural stability when subjected to 5 consecutive heating/cooling cycles to 800 • C. Maximums of relative elongations recorded for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…36 It can be concluded that the Zr from the CuCrZr alloy did not react with the ZrB 2 and no intermetallic phases could be formed. 23,24 But according to conclusions in References 37 and 38 the Zr, from the CuCrZr alloy might adsorb at the ceramics-metal interface and in this way it might promote wetting. In the case of the liquid Cu matrix, interactions at the interface might occur due to the slight dissolution of the ZrB 2 into the liquid metal and subsequent deposition of the Zr on the interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 It can be concluded that the Zr from the CuCrZr alloy did not react with the ZrB 2 and no intermetallic phases could be formed. 23,24 But according to conclusions in References 37 and 38 the Zr, from the CuCrZr alloy might adsorb at the ceramics-metal interface and in this way it might promote wetting. In the case of the liquid Cu matrix, interactions at the interface might occur due to the slight dissolution of the ZrB 2 into the liquid metal and subsequent deposition of the Zr on the interface.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Only few authors presented a liquid metal infiltration technology as a possible route for preparation of Cu-ZrB 2 composites. 23,24 The authors analyzed thermal behavior of two types of composites where different type of the metal matrix was used, the Cu and CuCrZr. They observed a higher thermal stability of the CuCrZr matrix infiltrated composite, which was thermally cycled between 30°C and 800°C.…”
Section: Introductionmentioning
confidence: 99%